2020
DOI: 10.1016/j.midw.2019.102578
|View full text |Cite
|
Sign up to set email alerts
|

The Labour Progression Study (LaPS): Duration of labour following Zhang's guideline and the WHO partograph – A cluster randomised trial

Abstract: Objective: To investigate labour duration in different phases of labour when adhering to Zhang's guideline for labour progression compared with the WHO partograph.Design: A secondary analysis of a cluster randomised controlled trial.Setting: Fourteen Norwegian birth care units, each with more than 500 deliveries per year constituted the clusters.Participants: A total of 7277 nulliparous women with singleton foetus in a cephalic presentation and spontaneous onset of labour at term were included.Intervention: Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…For instance, nulliparous women in this cohort had two hours longer duration at the 95 th percentile when we included those who delivered by CS vs. findings when those with CS and adverse neonatal outcome were excluded. These results correspond with findings of the LAPS Study which showed that women who delivered by intrapartum cesarean delivery had a prolonged labor duration compared with those who delivered vaginally in both study groups [43]. Future research is needed to better understand if labor duration or other factors, such as fetal malposition, may signal risk for cesarean delivery and/or adverse neonatal outcome.…”
Section: Labor Progression For All Women (Including Cesarean Delivery)supporting
confidence: 83%
“…For instance, nulliparous women in this cohort had two hours longer duration at the 95 th percentile when we included those who delivered by CS vs. findings when those with CS and adverse neonatal outcome were excluded. These results correspond with findings of the LAPS Study which showed that women who delivered by intrapartum cesarean delivery had a prolonged labor duration compared with those who delivered vaginally in both study groups [43]. Future research is needed to better understand if labor duration or other factors, such as fetal malposition, may signal risk for cesarean delivery and/or adverse neonatal outcome.…”
Section: Labor Progression For All Women (Including Cesarean Delivery)supporting
confidence: 83%
“…Inclusion was restricted to Norwegian‐speaking women. Results from the LaPS were recently published 15‐17 …”
Section: Methodsmentioning
confidence: 99%
“…Duration of labour varies between and within populations 1 3 . Determining normal and abnormal labour duration is complex because duration is influenced by multiple factors, such as: spontaneous or induced start of labour 4 , 5 , parity 2 , obstetrical management 6 9 , infant and maternal anthropometrics such as body mass index (BMI) and maternal age 10 17 .…”
Section: Introductionmentioning
confidence: 99%